Correlation Between Self-Efficacy and Motivation of English Teachers, Towards Students’ Achievement in Yogyakarta, Indonesia - Dari, Bayun Ulan; Putro, Nur Hidayanto Pancoro Setyo (Jurnal Pendidikan Progresif, 2021)
Correlation Between Self-Efficacy and Motivation of English Teachers, Towards Students’ Achievement in Yogyakarta, Indonesia. Objectives: This study was a correlational study that aimed to find out the correlations among three variables namely teacher self-efficacy, teacher motivation, and students’ achievement. Methods: The teacher self-efficacy scale (TSES) and English teacher motivation scale (ETMS) were distributed to 70 English teachers of junior high schools in Yogyakarta, and students’ average scores were collected as the students’ achievement. Findings: This research showed there were a significant correlation and contribution between teacher self efficacy and teacher’s motivation to students’ achievement. Conclusion: The higher the teacher’s self-efficacy, the higher the teacher’s motivation and the better the students’ achievement. Therefore, increasing teacher self-efficacy is very crucial because it relates to many educational outcomes such as teacher motivation and students’ achievement. Keywords: teacher self-efficacy, motivation, students’ achievement DOI: http://dx.doi.org/10.23960/jpp.v11.i1.202107